2023
DOI: 10.3389/fpsyg.2023.1190546
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of future-oriented thinking on academic outcomes

Simon Pawlak,
Ahmed A. Moustafa

Abstract: Future-oriented thought is a broad construct that characterize the ability to generate mental representations of the future and project oneself into a variety of hypothetical states. It is well established that the degree to which one is focused more on the past, present, or future has a variety of implications on psychological functioning. This study focuses on the relationship between future-oriented thought and academic performance of students. To bridge this gap, we conducted the first systematic review in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
2
2
0
1
Order By: Relevance
“…This finding aligns with prior studies that have established positive associations between selfefficacy and academic achievement [69,70]. Moreover, the literature has consistently linked future orientation [53,58], and especially work and career future orientation [4,54,55], to academic achievement.…”
Section: Relationships Between Future Orientation Self-efficacy and A...supporting
confidence: 90%
See 2 more Smart Citations
“…This finding aligns with prior studies that have established positive associations between selfefficacy and academic achievement [69,70]. Moreover, the literature has consistently linked future orientation [53,58], and especially work and career future orientation [4,54,55], to academic achievement.…”
Section: Relationships Between Future Orientation Self-efficacy and A...supporting
confidence: 90%
“…In addition, the positive correlation between work/career future orientation and academic achievement, even if modest, contributed to a predictive power of the former for the latter. The role of these two predictors is consistent with the studies that have demonstrated the crucial role of self-efficacy [71] and future orientation [58] in high school students' academic achievement.…”
Section: Self-efficacy and Work/career Future Orientation Predict Aca...supporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, it is important to develop a positive future orientation in students because it has a positive impact on their success in their studies and their future. The study by Pawlak and Moustafa (2023) indicated that higher degrees of future orientation were associated with higher levels of involvement, attendance, and GPA. This implies that those with a future-focused orientation are probably going to perform well in educational environments.…”
Section: Future Orientationmentioning
confidence: 98%
“…Участь студентів у громадському житті закладу вищої освіти є дуже важливою. Студенти, залучені до діяльності університетських клубів і спільнот, є більш самостійними, ніж інші, і створюють міцнішу мережу соціальних стосунків, що сприяє їхній незалежності, прихильності університету й активному зануренню в освітній процес (Pawlak & Moustafa, 2023). Таким чином, це можна розглядати в контексті можливостей для студентів (Universities UK, 2016):…”
Section: неакадемічний студентський досвід: послуги для студентівunclassified